The Implementation of Scientific Approach in Building Students’ Critical Thinking Skills Through Teaching The Subject of Islamic Education and Character Building at SMK Negeri 1 Bojonegoro - muhammad Ansorul Hakim; Zainuddin Maliki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
This research discusses how the implementation of scientific approach influences in building students' critical thinking skills on the subjects of Islamic Education and Character building at SMK Negeri 1 Bojonegoro. A combination method called concurrent embedded strategy is used in this research in which quantitative method is used as the primary method and qualitative method is used as the secondary method. The population in this study are 1440 students at SMK Negeri 1 Bojonegoro. Meanwhile, three classes (93 students) of Accounting major in grade XI are the subject of the research. Purposive sampling is used as sampling technique. Data are collected by using observation, interview, questionnaires, and documentation techniques. The data are analyzed by statistic product moment. The result of research showed that = 0,404, when it consulted with r value in table for N = 93, with significance level 5% = 0,202 and 1% = 0,263. So in a significance level of 5% the value is greater than the value, and in a significance level of 1% the value is also greater than the value. When it consulted with the amount of